The impact of agricultural package programs on farm productivity in Tigray-Ethiopia: Panel data estimation - Teka Araya Mebrahtu; Sung-kyu Lee (Cogent Economics & Finance, 2019)
Ethiopian government has introduced various agricultural package programs in promoting agricultural productivity of the smallholder farmers. The paper attempts to explore the status and determinants of agricultural productivity and estimate the impact of integrated agricultural package programs on farm productivity by using extensive panel data in the Eastern zone of Tigray in Ethiopia. Thus far, there have been no researches attempted to analyze the impact of the integrated agricultural package programs introduced to the farmers on various outcome variables in Tigray region in Ethiopia by using panel data. In doing so, we used two estimation methods: (i) the fixed effect (FE) estimation model to empirically evaluate the impact of household-based agricultural package programs on farm productivity in Tigray region, and (ii) the propensity score matching (PSM) method to estimate the average treatment effect on the treated (ATT). Our econometric estimates show the following two practical results. Firstly, household-based agricultural package programs have a positive and statistically significant impact on farm productivity in the Eastern zone of Tigray. This implies that the agricultural household package participant households have higher productivity than the non-beneficiaries. Secondly, the PSM estimation result ensures that the ATT is positive and statistically significant for the package participant smallholder farmers. In the end, these outcomes provide governments with some useful guides to promote farm productivity in Tigray, Ethiopia.
Keywords: D13; N50; O13; Q15; Q1; 330; ATT; agricultural package; Ethiopia; fixed effect; productivity; PSM